Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) x (x+1) (x-1) - (x-1) (x2+x+1)= x3 - x2 + x2 - x - x3 + 13
= 1- x
Với a,b,c khác 0 và a+b+c=0 ta có
\(A=\frac{ab}{a^2+b^2-c^2}+\frac{bc}{b^2+c^2-a^2}+\frac{ca}{c^2+a^2-b^2}=\frac{ab}{\left(a+b\right)^2-2ab-c^2}+\frac{bc}{\left(b+c\right)^2-2bc-a^2}+\frac{ca}{\left(c+a\right)^2-2ca-b^2}=\frac{ab}{\left(a+b+c\right)\left(a+b-c\right)-2ab}+\frac{bc}{\left(b+c+a\right)\left(b+c-a\right)-2bc}+\frac{ca}{\left(c+a+b\right)\left(c+a-b\right)-2ca}=\frac{ab}{-2ab}+\frac{bc}{-2bc}+\frac{ca}{-2ca}=-\frac{1}{2}+-\frac{1}{2}+-\frac{1}{2}=-\frac{3}{2}\)
Vậy A=-3/2
Bài 1:
Ta có: \(A=\left(2+1\right)\left(2^2+1\right)\left(2^4+1\right)...\left(2^{256}+1\right)+1\)
\(=\left(2-1\right)\left(2+1\right)\left(2^2+1\right)\left(2^4+1\right)...\left(2^{256}+1\right)+1\)
\(=\left(2^2-1\right)\left(2^2+1\right)\left(2^4+1\right)...\left(2^{256}+1\right)+1\)
\(=\left(2^4-1\right)\left(2^4+1\right)...\left(2^{256}+1\right)+1\)
\(............................\)
\(A=\left[\left(2^{256}\right)^2-1\right]+1=2^{512}\)
$(a+b+c)(a^2+b^2+c^2-ab-bc-ca)$
$=(a^3+ab^2+ac^2-a^2b-abc-a^2c)+(ba^2+b^3+bc^2-ab^2-b^2c-abc)+(ca^2+cb^2+c^3-abc-bc^2-c^2a)$
$=a^3+b^3+c^3-3abc$
\(\left(a+b+c\right)\left(a^2+b^2+c^2-ab-bc-ca\right)=a^3+ab^2+ac^2-a^2b-abc-a^2c+ba^2+b^3+bc^2-ab^2-b^2c-abc+a^2c+b^2c+c^3-abc-bc^2-ac^2=a^3+b^3+c^3-3abc\)
b: \(\Leftrightarrow2a^2+2b^2+2c^2-2ab-2bc-2ac=0\)
\(\Leftrightarrow\left(a^2-2ac+c^2\right)+\left(a^2-2ab+b^2\right)+\left(b^2-2bc+c^2\right)=0\)
=>(a-c)^2+(a-b)^2+(b-c)^2=0
=>a=b=c
c: \(\Leftrightarrow a^2+b^2+c^2-ab-ac-bc=0\)
\(\Leftrightarrow2a^2+2b^2+2c^2-2ab-2bc-2ac=0\)
\(\Leftrightarrow\left(a^2-2ac+c^2\right)+\left(a^2-2ab+b^2\right)+\left(b^2-2bc+c^2\right)=0\)
=>(a-b)^2+(a-c)^2+(b-c)^2=0
=>a=b=c
= (a+b+c)3